Meta-Analysis: The Effect of Screen Time and Fast-Food Intake on Obesity in Children and Adolescents - Salwa Annisaa; Yulia Lanti Retno Dewi; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Obesity has reached epidemic proportions worldwide, making obesity a serious global public health challenge. Obesity is not only found in adults but also in children and adolescents which can lead to various physical and mental health problems that are detrimental to the quality of life and are very risky into adulthood. Obesity in children and adolescents today is caused by a lifestyle that makes a person increase in consuming fast food, lack of sleep and the longer duration of screen time. This study aims to analyze the effect of screen time and fast food on obesity in children and adolescents.Subjects and Method: This was a systematic review and meta-analysis. Population= children and adolescents, Intervention= screen time and fast food, Comparison= no screen time and no fast food, Outcome= obesity. Article searches through journal databases include: PubMed, Science Direct, Google Scholar and Springerlink. The articles used in this study are articles that have been published from 2011-2021. The keywords used are obesity OR obese OR overweight AND “fast foods” OR snacks OR “fried foods” AND “social media” OR “screen time” OR television AND child OR adolescent. Articles were selected with the help of PRISMA flow diagrams. The inclusion criteria included full-text articles with a cross-sectional study design. The analysis used logistic regression with adjusted odds ratio and published in English. Articles that have met the requirements are analyzed using the Revman 5.3 application.Results: Fifteen articles came from Nepal, China, Pakistan, Canada, Darussalam, Ethiopia, Italy, Australia, Indonesia. Meta-analysis of 8 cross-sectional studies showed that screen time 3 hours/ day can affect obesity in children and adolescents 2.4 times compared to screen time < 3 hours/ day. The results of the meta-analysis in 8 cross-sectional studies showed that fast food 3 times/ week had an effect on obesity in children and adolescents by 2.74 times compared to fast food < 3 times/week.Conclusion: The long duration of screen time and the frequency of consuming fast food often increase the risk of obesity in children and adolescents.Keywords: obesity, screen time, fast foods, meta-analysisCorrespondence:Salwa Annisaa. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: salwaannisaa@gmail.com. Mobile: 081541180488.Journal of Health Promotion and Behavior (2021), 06(02): 164-175DOI: https://doi.org/10.26911/thejhpb.2021.06.03.01